ANALISIS MINAT, MOTIVASI, PEKERJAAN YANG DIHARAPKAN, & LINGKUNGAN BELAJAR TERHADAP KEPUTUSAN MAHASISWA MEMILIH PROGRAM S1 FAKULTAS EKONOMI (Studi Pada Mahasiswa Ekonomi Di Perguruan Tinggi Kota Bengkulu) - Meilaty Finthariasari; Diana Dewi Saputri (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
This study aims to determine the factors that influence student decisions to choose the Faculty of Economics. This research is a quantitative study with a sample of 356 respondents. The sampling technique used in this study was to use the Slovin formula. Data collection techniques using observations and questionnaires. The collected data was then processed using the SPSS 21 data processing tool and analyzed using the classical assumption test analysis technique, multiple linear regression, the coefficient of determination (R2) and hypothesis testing. The results of this study can be seen from the multiple linear regression test, namely Y = 1.001 + 0.141X1 + 0.103X2 + 0.288X3 + 0.057X4 + e. From the results of the partial hypothesis test (T test) that each variable of interest, motivation, expected work, and learning environment has a significant positive effect on the student decision variable to choose the Faculty of Economics. While the simultaneous test results (F test) between the independent variables on the dependent variable have a significant effect.Keywords: Interests, Motivation, Expected Work, Learning Environment, and student decisions to choose the Faculty of Economics